2014
DOI: 10.1002/pssa.201330517
|View full text |Cite
|
Sign up to set email alerts
|

Double-layer effect on electrothermal properties of transparent heaters

Abstract: Phone: þ82 10 8717 0978, Fax: þ82 2 958 5229 Transparent double-layer heaters that consist of aluminumdoped zinc oxide and fluorine-doped tin oxide films are prepared by electron cyclotron resonance-metal organic chemical vapor deposition and RF-sputtering systems, in sequence. The double-layered transparent conducting oxide film is designed and prepared to achieve both of high conductivity and high-temperature performance. This double-layer structure has lower sheet resistance, due to the grain size increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Kim et al explored the use of bilayers by combining AZO and FTO deposited by sputtering and chemical vapor deposition (CVD), respectively. [ 84 ] They observed that both conductivity and transparency improved for bilayers with respect to single layers of the same thickness, as demonstrated in Figure 5e. [ 84 ] This is attributed to the higher overall particle size in the film, which affects both mobility and transparency.…”
Section: The Investigated Materials Technologies For Transparent Heatersmentioning
confidence: 90%
See 4 more Smart Citations
“…Kim et al explored the use of bilayers by combining AZO and FTO deposited by sputtering and chemical vapor deposition (CVD), respectively. [ 84 ] They observed that both conductivity and transparency improved for bilayers with respect to single layers of the same thickness, as demonstrated in Figure 5e. [ 84 ] This is attributed to the higher overall particle size in the film, which affects both mobility and transparency.…”
Section: The Investigated Materials Technologies For Transparent Heatersmentioning
confidence: 90%
“…As a first approximation, this value does not depend much on the material that composes the TH. Accordingly, this range of τ values was observed for THs composed of AgNW networks, [ 45 ] CNT networks, [ 27 ] TCO, [ 84 ] conductive polymers, [ 50 ] electrospun nanofibers, [ 76,85 ] or graphene. [ 86 ] For efficient THs, the τ value mainly depends on the characteristics of the substrate: the thinner the substrate, the shorter the characteristic time.…”
Section: Principle Of Thsmentioning
confidence: 93%
See 3 more Smart Citations